Development and evaluation of a composite supercapacitor-based 12 V transient start–stop power system for vehicles: Modelling, design and fabrication scaling up. (June 2021) - Lei, Chunhong; Fields, Richard; Wilson, Peter; Lekakou, Constantina; Amini, Negar; Tennison, Stephen; Perry, John; Gosso, Michele; Martorana, Brunetto
The study involves a bottom-up approach, from bottom cells to large supercapacitor pouch cells, encompassing the design, modelling and fabrication stages of the cells leading to a 12 V transient start–stop (TSS) power system for automotive applications. More specifically, the design of a large composite supercapacitor is presented, consisting of a high power density component and a high energy density component, hybridised at material level. The composition of the composite supercapacitor is optimised to be application-specific so that it satisfies a specified energy-to-maximum power ratio for the 12 V TSS system. The testing of the large composite supercapacitor pouch cells and the 12 V TSS system proves the validity of the bottom-up approach, validates the design and the proposed electric circuit model and its parameters, fitted according to experimental data of small laboratory cells and applied successfully to the large cells, and proves the high quality of the scaled-up fabrication processes. The 12 V TSS power system of seven large composite supercapacitor cells satisfies the set criteria of energy and maximum power for the specified duration, 15 Wh and 4.2 kW respectively, at a total mass of 3.94 kg, below the original set limit of 5 kg.